2017
DOI: 10.3332/ecancer.2017.783
|View full text |Cite
|
Sign up to set email alerts
|

Do we need regional guidelines for breast cancer management in the MENA region? MENA Breast Cancer Guidelines project

Abstract: PurposeBreast cancer is the most common cancer among females worldwide in general and in the Middle East and the North African region (MENA region) in particular. Management of breast cancer in the MENA region faces a lot of challenges, which include younger age at presentation, aggressive behaviour, lack of national breast screening programmes and lack of reliable data registries as well as socioeconomic factors. These factors make applying the international guidelines for breast cancer management very challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
1
4
0
Order By: Relevance
“…(2015) who wrote a scientific report in KSA found that FDAP really improves MCQs writing, which supports our findings, since it is within the same context [39], together with other findings in USA items writing for USMLE [40]. Positive perceptions found include:…”
Section: Discussionsupporting
confidence: 86%
“…(2015) who wrote a scientific report in KSA found that FDAP really improves MCQs writing, which supports our findings, since it is within the same context [39], together with other findings in USA items writing for USMLE [40]. Positive perceptions found include:…”
Section: Discussionsupporting
confidence: 86%
“…A study of the rural areas of Iran demonstrated that the cost-effectiveness of screening programs significantly depended on the extent of participation, highlighting the importance of focusing on improving knowledge and acceptance ( 40 ). Almost all MENA countries lack a nationally organized cancer screening program and have numerous cultural and socioeconomic barriers toward screening ( 5 , 41 , 42 ). A review article of breast cancer epidemiology in Iran reported that only about 18% of cases were detected in stage I ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was driven by data from a survey conducted on 600 oncologists in the MENA region, at which only 21% of the participating oncologists have genetic counseling services available in their health-care facilities. 9 Countries of the LMICs/MENA region lack proper national disease/ patient registries. Available data registries are merely hospital-based where its data cannot be generalized or represent the burden of disease on country level.…”
Section: Plans For Lmics/menamentioning
confidence: 99%
“…Available data registries are merely hospital-based where its data cannot be generalized or represent the burden of disease on country level. 9 All panel members (100%) agreed that national, population-based cancer registries, as well as other relevant surveys and data collection tools (including data collected from any available BC control programs, or developing registries that cover specific populations, or utilizing incidence and mortality rates from ongoing registries or data linkage between the available registries) should be used to collect high-quality population-based incidence and mortality data on BC, for all age groups, to properly guide policies and plans. Identifying the most important data that need to be collected or included in the registry and the most efficient and cost-effective way of collecting these data should be the first step to work on.…”
Section: Plans For Lmics/menamentioning
confidence: 99%
See 1 more Smart Citation